The Effect of Work Environment and Incentives On Employee Performance PT. Via Motif Tasikmalaya - Mohamad Irsan Nazar; Kusuma Aghdi Rahwana; Dudu Risana (CV. Ulil Albab Corp, 2023)
This study aims to determine and analyze the influence of the work environment and incentives both simultaneously and partially on the performance of employees at PT. Via Tasikmalaya Motif. The method used in this research is a survey with a descriptive approach. With a research sample of 100 employees as respondents. The data used is using primary data. The analytical tool used in this study is multiple linear regression using the SPSS version 25 support application. The test results show that partially the variables used in the study, namely the work environment and incentives, have a significant effect on employee performance at PT. Via Tasikmalaya Motif. Simultaneously there is a significant influence of the work environment and incentives together on employee performance.